Phytochemical Screening, GCMS, FTIR profile of Bioactive Natural Products in the methanolic extracts of Cuminum cyminum seeds and oil - Ramya, S.; Loganathan, T.; Chandran, M.; Priyanka, R.; Kavipriya, K.; Grace Lydial Pushpalatha, G.; Aruna, Devaraj; Ramanathan, L.; Jayakumararaj, R.; Saluja, Vikrant (Journal of Drug Delivery and Therapeutics, 2022)
Seeds of cumin (Cuminum cyminum L.) are widely used as a spice for their distinctive aroma. C. cyminum have been used in traditional medicine to treat a variety of diseases. Literature presents ample evidence for biomedical activities of cumin which is attributed to its bioactive secondary metabolites - terpenes, phenols, and flavonoids. Besides, health effects of cumin seeds have been experimentally validated through phytochemical analysis depicting the presence of a wide array of bioactive secondary metabolites (BASMs) viz., alkaloid, coumarin, anthraquinone, flavonoid, glycoside, protein, resin, saponin, tannin and steroid. Pharmacological studies indicate that BASMs in seeds of C. cyminum exert antimicrobial, insecticidal, anti-inflammatory, analgesic, antioxidant, anticancer, antidiabetic, anti-platelet-aggregation, hypotensive, bronchodilatory, immunological, contraceptive, anti-amyloidogenic, anti-osteoporotic, aldose reductase, α-glucosidase and tyrosinase inhibitory effects. In the present study phytochemical screening, GCMS, FTIR profile of bioactive natural products from C. cyminum has been envisaged. Phytochemical screening revealed the presence of alkaloids, anthraquinones, carbohydrates, coumarins, flavonoids, glycosides, proteins, quinones, saponins, steroids, tannins and terpenoids. GC-MS analysis revealed the presence of 21 compounds, of which Cuminaldehyde was prominent. FTIR analysis showed the presence of a strong peak value for 15 compounds and medium peak value for 6 compounds. Many of the compounds in the list could be ADMET bioprospected for biomedical applications as natural drug leads. Keywords: Cuminum cyminum; Cuminaldehyde; Bioactive Natural Products; GCMS; FTIR